Developing design principles for the digitalisation of purchasing and supply management. Issue 1 (January 2019) - Srai, Jagjit Singh; Lorentz, Harri
Abstract: This paper develops an approach to evaluating designs for digitalisation interventions in purchasing and supply management (PSM), and identifies some fundamental design principles for such interventions. A set of advanced technologies for digitalisation and a theory-based set of seven value drivers for PSM are identified for the proposed grid to facilitate the design of applications and interventions for digitalising PSM. The grid relates the digital technologies to the PSM value drivers in a matrix-like manner, allowing the structured consideration of the space defined by these two dimensions. The proposed approach to the strategic evolution of digitalisation in PSM is tested and its utility is demonstrated in analyses of practitioner literature and multiple case-study-based perspectives on PSM digitalisation. Two fundamental design principles relating to the use of the grid, or to the filling of its space, are set out, thus the research provides new theoretical perspectives on the design of advanced forms of PSM digitalisation. The proposed grid may be used in application design, communicating current and future states of PSM digitalisation to stakeholders, and specifically in developing a future-oriented strategy with a digitalization element for the PSM function. Highlights: A grid, linking digital technologies with PSM value drivers is proposed. Two fundamental design principles are stated for designing digital interventions. We provide theoretical perspectives on the design of advanced digitalization of PSM. The grid is useful in designing, communicating and strategizing digitalization in PSM.